2016
DOI: 10.18632/oncotarget.13941
|View full text |Cite
|
Sign up to set email alerts
|

LHBs can elevate the expression of MDR1 through HIF-1α in patients with CHB infection: a comparative proteomic study

Abstract: Background and Aims: Hepatitis B virus (HBV) infection is a major risk factor for liver cirrhosis and hepatocellular carcinoma (HCC). To gain a better understanding of the pathogenesis of HBV infection, this study aimed to investigate the differentially expressed proteins (DEPs) in liver tissues from patients with chronic hepatitis B (CHB) infection.Results: Seventy-one DEPs were identified. Overexpression of multi-drug

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Furthermore, physiological substances including steroid hormones, environmental stresses such as temperature, osmotic pressure and pH, and xenobiotics such as insecticides, heavy metal and DNA damage reagents have been shown to significantly modulate ABCB1 expression in vitro 45 . Interestingly, human pathogenic virus and virus proteins are also reported to induce ABCB1 expression 49,50 . Since bats are renowned for being a reservoir of high mortality viruses like Ebola 51 and SARS 52 , some viral proteins may induce ABCB1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, physiological substances including steroid hormones, environmental stresses such as temperature, osmotic pressure and pH, and xenobiotics such as insecticides, heavy metal and DNA damage reagents have been shown to significantly modulate ABCB1 expression in vitro 45 . Interestingly, human pathogenic virus and virus proteins are also reported to induce ABCB1 expression 49,50 . Since bats are renowned for being a reservoir of high mortality viruses like Ebola 51 and SARS 52 , some viral proteins may induce ABCB1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis is thought to depend on a perfectly coordinated balance between endogenous-positive and negative regulatory factors. The investigation of HIF-1α, VEGF and Ang-2 levels in sera of patients with benign or malignant chronic liver diseases suggested that their synchronous increasing expression from normal control, chronic hepatitis, liver cirrhosis to HCC [27,28] .…”
Section: Discussionmentioning
confidence: 99%
“…ATP-binding cassette (ABC) transporters, such as MDR1, can pump chemotherapeutic drugs from the intracellular to extracellular regions of HCC cells to produce drug resistance. The reporter gene assay and electrophoretic mobility shift assay proved that HIF-1α is a critical factor for MDR1 gene overexpression ( 162 ); and (d) apoptosis inhibition. HIF-1α is the promoter activator of CBR1, and CBR1 overexpression induces apoptosis resistance by reducing oxidative stress associated with hypoxia, cisplatin, and doxorubicin treatment ( 163 ).…”
Section: Mechanisms Of Therapeutic Resistance In the Hcc Microenviron...mentioning
confidence: 99%